From Russia with Code : Programming Migrations in Post-Soviet Times - Lepinay, Vincent Antonin; Biagioli, Mario, 1955- (Book collections on Project MUSE., 2019)
The contributors to From Russia with Code examine Russian computer scientists, programmers, and hackers in and outside of Russia within the context of new international labor markets and the economic, technological, and political changes in post-Soviet Russia.